THE ADVANTAGES OF MIND MAPPING IN TEACHING READING - Novianty, Melisa (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2022)
Reading is an interaction between a reader and a piece of text. Reading is easy to do by some people but in fact, study about readin is difficult. Therefore, the teacher should choose one of the methods to make students interesting in reading. Therefore, this paper highlights the advamtages of mind mapping in teaching reading. As addition, in this context that reading will be used by using mind mapping then it can be designed by pictures, circles or boxs after reading the text depend on the ways of thinking and the creativity in create it.